Comparison of Perinatal Outcome of Preterm Births Starting in Primary Care versus Secondary Care in Netherlands: A Retrospective Analysis of Nationwide Collected Data. (30th December 2014) - van der Ven, A. J.; Schaaf, J. M.; van Os, M. A.; de Groot, C. J. M.; Haak, M. C.; Pajkrt, E.; Mol, B. W. J.
Abstract : Introduction . In Netherlands, the obstetric care system is divided into primary and secondary care by risk level of the pregnancy. We assessed the incidence of preterm birth according to level of care and the association between level of care at time of labor onset and delivery and adverse perinatal outcome. Methods . Singleton pregnancies recorded in Netherlands Perinatal Registry between 1999 and 2007, with spontaneous birth between 25 +0 and 36 +6 weeks, were included. Three groups were compared: (1) labor onset and delivery in primary care; (2) labor onset in primary care and delivery in secondary care; (3) labor onset and delivery in secondary care. Multivariable logistic regression analyses were performed to calculate the risk of perinatal mortality and Apgar score ≤4. Results . Of all preterm deliveries, 42% had labor onset and 7.9% had also delivery in primary care. Women with labor onset between 34 +0 and 36 +6 weeks who were referred before delivery to secondary care had the lowest risk of perinatal mortality (aOR 0.49 (0.30–0.79)). Risk of perinatal mortality (aOR 1.65; 95% CI 1.20–2.27) and low Apgar score (aOR 1.95; 95% CI 1.53–2.48) were significantly increased in preterm home delivery. Conclusion . Referral before delivery is associated with improved perinatal outcome in the occurrence of preterm labor onset in primary care.